Clinical direct posterior restoration in aesthetic and functional aspect - A. V. Mitronin; D. A. Ostanina; Kh. N. Eshnazarov (LLC "Endo Press", 2022)
Direct restoration is one of the most common methods of rehabilitation of defects in teeth hard tissues. Composite nano-ceramic restorations are an alternative to traditional prosthetic treatment in view of the growing demand for minimally invasive technologies, since crowns or other prosthetic restorations imply a significant loss of tooth structure with macro-mechanical and more invasive preparation of the dental tissues. This article represents a clinical case of direct composite restoration in carious teeth 3.6,3.7 with aesthetic and functional rehabilitation of contact points.